A rare cause of multiple small bowel ulcers and strictures in a 10-year-old child - Kijmassuwan, Teera; Tanpowpong, Pornthep; Molagool, Sani; Treepongkaruna, Suporn (Turkish Journal of Gastroenterology, 2018)
Abstract Enteritis and small bowel ulcers can be caused by inflammatory bowel disease, drug-induced enteritis, cytomegalovirus, tuberculosis, or intestinal lymphoma. Cryptogenic multifocal ulcerous stenosing enteritis (CMUSE) is an uncommon idiopathic cause of ulceration and stricture of the small bowel. CMUSE can occur in adults, but only few pediatric cases have been reported. Inflammatory bowel disease and other causes should be carefully sought first before the diagnosis of CMUSE can be made. Previous reports demonstrated that surgical intervention may be necessary for both diagnostic and therapeutic purposes. With regard to the management, systemic corticosteroids may help, and surgery plays a role in patients present with signs of intestinal obstruction. We report a young girl who presented with a prolonged history of refractory iron deficiency anemia with protein-losing enteropathy without other obvious gastrointestinal symptoms. She underwent several laboratory and endoscopic investigations as well as histopathology of the resected full-thickness small bowel area before a proposed diagnosis of CMUSE was made. A trial of immunosuppression (both prednisolone and azathioprine) was initiated that provided a relatively satisfactory result. Cite this article as: Kijmassuwan T, Tanpowpong P, Molagool S, Treepongkaruna S. A rare cause of multiple small bowel ulcers and strictures in a 10-year-old child. Turk J Gastroenterol 2018; 29: 108-11.